Perbandingan SQL dan NoSQL: Studi Literatur Tentang Keunggulan, Kelemahan, dan Penerapannya - Chandra Ramadhan; Mamok Andri Senubekti; Suhendri Suhendri (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
A database is a fundamental element in an information system that is used to manage and store data. Two commonly used database types are NoSQL (Not Only SQL) and SQL (Structured Query Language). SQL uses a structured relational model with a fixed schema, while NoSQL is more flexible with various storage models such as document, key-value, column-width, and graph. This research aims to conduct a literature study on the comparison of these two types of databases, including their advantages, disadvantages, and applicability in various information system scenarios. The study results show that the choice between SQL and NoSQL is highly dependent on the specific needs of the application, in terms of performance, scalability, and data complexity.